Application Of Module Educational Technology in Teaching Economic and Social Geography in Surkhandarya Region (Eurasian Journal of History, Geography and Economics, 2021)
Application of modular educational technology in teaching economic and social geography in Surkhandarya region, which considers modular teaching methods.